Desian Digital Crossword Puzzle Berbasis STEM Materi Pencernaan Manusia Untuk Meningkatkan Literasi Sains Siswa Kelas 5 SDN Kepanjenkidul 2 Kota Blitar - Mohamad Fatih (Universitas Nahdlatul Ulama Blitar, 2026)
This study aimed to develop a STEM-based digital crossword puzzle learning media, assess its validity and feasibility, and determine its effectiveness in enhancing scientific literacy among fifth-grade elementary school students studying the human digestive system. The research adopted the ADDIE development framework, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. Validation and practicality assessments involved media experts, content experts, teachers, and students. Data were collected using structured questionnaires and analyzed descriptively. The results indicated that the developed media achieved a validity score of 94% from media experts and 98% from content experts, both categorized as highly valid. Teacher evaluations yielded a feasibility score of 96%, demonstrating excellent practicality. In addition, the N-Gain score of 0.97 obtained from student responses reflected a high level of improvement in scientific literacy. These findings suggest that the STEM-based digital crossword puzzle is a valid, practical, and effective learning medium for fostering scientific literacy in elementary school education.